Electrodeposition Kinetics of Ni/Nano-Y2O3 Composite Coatings - Xinyu Zhou; Yiyong Wang; Xianglin Liu; Zhipeng Liang; Hui Jin (Metals, 2018)
Ni/nano-Y2O3 composite films were successfully prepared by electrochemical deposition using an acid sulfamate bath. The influence of solid particles added to electrolyte on electrodeposition was investigated by electrochemical measurement methods. The linear sweep voltammetry test showed that the composite deposition took place at a greater potential than that of nickel, and the presence of nano-Y2O3 decreased cathodic polarization. Chronoamperometry studies indicated that the nucleation model of both deposits similarly approached the theoretical instantaneous nucleation mode based on the Scharifker–Hills model. The Y2O3 particles adsorbed on the cathodic surface were shown to facilitate the nucleation/growth of the nickel matrix which is consistent with the deposition kinetics parameters calculated by non-linear fitting experimental curves. The results of electrochemical impedance spectroscopy showed that the presence of Y2O3 particles in a bath is beneficial for the decrease in charge transfer resistance in the deposition. The atomic force microscopy observations of both deposits obtained in the initial electrodeposition stage confirmed that the Ni-Y2O3 composite had a higher grain number and finer mean grain size.